Biométria de frutos e sementes de Luetzelburgia auriculata (Allemão) Ducke - Barroso, Roberto Ferreira; Silva, Francisco de Assis; Nobrega, Jackson Silva; Silva, Luanderson José da Silva e; Novaes, Danilo Brito; Ferreira, Vinicius Staynne (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2016)
A Caatinga apresenta uma grande diversidade de espécies vegetais, dentre elas Luetzelburgia auriculata é uma das espécies predominantes no bioma, desempenhando papel fundamental para o ecossistema local. Este trabalho objetivou descrever as características biométricas de frutos e sementes de Luetzelburgia auriculata. Para a descrição das características da semente foram coletados 200 frutos e 200 sementes de plantas nativas do município de Santa Helena, Paraíba. As amostras foram encaminhadas ao Laboratório de Nutrição Mineral de Plantas do Centro de Saúde e Tecnologia Rural de Universidade Federal de Campina Grande para a realização das devidas aferições biométricas. Os frutos foram analisado pelo comprimento, espessura superior, mediana e inferior; largura superior, mediana e inferior. Para as sementes, foram analisados comprimento, espessura e a largura. Verificou-se que o comprimento dos frutos variou de 50,7 a 98,2 cm, a espessura de 6,00 a 17 mm e largura variando de 12,4 a 21,8 mm. Em relação às sementes, 46% se enquadraram na classe de comprimento com intervalo de 19,9 a 20,8 mm. A espécie Luetzelburgia auriculata apresentam variabilidade nas características biométricas de frutos e sementes Biometrics of fruit and seeds of Luetzelburgia auriculata (Allemão) Ducke Abstract: The Caatinga presents a great diversity of plant species, among them the woodpecker (Luetzelburgia auriculata (Allemao) Ducke.) is one of the predominant species in the biome, playing a fundament al role for the local ecosystem. This work aimed to describe the biometric characteristics of fruits and seeds of Pau de Pedra. For the description of the characteristics of the Luetzelburgia auriculata (Allemão) Ducke seed, 200 fruits and 200 seeds of native plants of the municipality of Santa Helena, Paraíba state were collected for biometry and seed mass. Afterwards they were packed in plastic bags and properly identified and taken to Laboratório de Nutrição Mineral de Plantas do Centro de Saúde e Tecnologia Rural Universidade Federal de Campina Grande, where the biometric measurements were continued. The fruit was analyzed for its length, the upper, median and inferior thickness; Upper, median and lower width. The seed was analyzed for length, thickness and width. It was verified that the length of the fruits varied from 50.7 to 98.2 cm, the thickness with 6.00 to 17 mm and width ranging from 12.4 to 21.8 mm. Regarding the seeds, 46% were in the length class with a range of 19.9 to 20.8 mm. From the evaluations we conclude that the species Luetzelburgia auriculata present variability in the biometric characteristics of fruits and seeds, and the morphological description of the fruit and the seed constitutes the importance of the species recognition.